Enteroparasites in Students at the Escuela Técnica Agropecuaria Robinsoniana “Caicara”, Caicara del Orinoco, Cedeño Municipality, Bolivar State, Venezuela - Rodolfo Devera; Ytalia Blanco; Ixora Requena; Rosa María Tedesco; José Alvarado; Nellys Alves; Richard Belisario (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2010)
To determine the prevalence of enteroparasites, 136 students attending the Escuela Técnica Agropecuaria Robinsoniana “Caicara”, Caicara del Orinoco, Cedeño Municipality, State of Bolivar, were assessed. A stool sample was collected for each student, which was analyzed by direct examination, Kato, Willis, spontaneous sedimentation and agar plate culture techniques. The prevalence of intestinal parasites was 89% (121/136). In all age groups, parasites were diagnosed (X2 = 3.873, f.d. = 3 p > 0.05). Both sexes were equally affected (p > 0.05). A total of 12 species of parasites and/or commensals were diagnosed. Protozoa were more prevalent (98.4%) than helminthes (30.0). Blastocystis hominis was the most prevalent intestinal parasite in 79.4%. In conclusion, results showed a high prevalence (89%) of intestinal parasitic infection in the population studied, with no predilection for sex or age, with prevalence for protozoa, particularly B. hominis. Sanitary and sanitation deficiencies could explain such high prevalence rates.